Pengaruh Terpaan Konten dan Celebrity Endorsement terhadap Konsumtif Remaja Muslim - Muhsyi Alyah; Andi Patimbangi; Fitriani Arief (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aimed to investigate the influence of content exposure and celebrity endorsement on the consumptive behavior of Muslim adolescents among students at MAN 1 Bone. The population for this research was students of MAN 1 Bone for the 2023/2024 academic year. The sampling technique employed was simple random sampling with a total of 100 respondents. Data was collected through the distribution of questionnaires and documentation. This research utilized an explanatory survey research method with a quantitative approach. The data analysis techniques used were statistical tests, including multiple linear regression, t-test, f-test, and the coefficient of determination (R2) test. The results revealed that: (1) There was no significant influence of content exposure on the consumptive behavior of MAN 1 Bone students. (2) Celebrity endorsement significantly influenced the consumptive behavior of MAN 1 Bone students. (3) Content exposure and celebrity endorsement had a significant influence on the consumptive behavior of MAN 1 Bone students. The combined effect of the content exposure and celebrity endorsement variables on the consumptive behavior variable of MAN 1 Bone students was 25.2%, while the remaining 72.8% was explained by other factors outside the two independent variables studied.